AN APPLICATION OF RESIDUE NUMBER SYSTEM ARITHMETICS TO SECURE HASH FUNCTIONS DESIGN - Pavlović, Milija; Panić, Stefan; Damjanović, Boris; Stamenković, Negovan (Bulletin of Natural Sciences Research, 2025)
This paper presents a cryptographic hash function based on the Residue Number System (RNS), designed to enhance security and computational efficiency. The function leverages the parallelism and modular properties of RNS to achieve high-speed processing while maintaining strong diffusion and resistance to various cryptanalytic attacks. Experimental results confirm that the proposed function exhibits a pronounced Avalanche effect, ensuring that minor changes in the input result in significant alterations in the hash output. Additionally, statistical analysis using the ENT test demonstrates a high level of entropy and uniform distribution of hash values, reinforcing the function’s unpredictability—an essential characteristic for cryptographic security. The proposed hash function is suitable for applications in digital signatures, data integrity verification, and authentication systems, offering advantages in environments requiring high computational efficiency.
Keywords: Cryptographic hash function; Residue number system; Avalanche effect; Diffusion; Entropy; Parallelism; Modular arithmetic